Grain quality characterization of Philippine low cost traded mill rice from milling to distribution - Alpapara, Noridel Paul Narvaez; Azanza, Ma. Patricia V. (2005.)
ABSTRACT This study was conducted to establish the compliance of the Philippine low-cost traded milled rice to the quality standards of the Philippine Grains Standardization Program (PGSP). A face-to-face interview of the city-based and municipality based rice millers in Nueva Ecija, Central Luzon, Philippines was done using the developed questionnaire to obtain information on the following: the type of milled rice used; pre-milling practices utilized; rice milling processes adopted; and product naming and pricing. This study also evaluated the grain quality of the low-cost traded milled rice from the various rice millers, wholesaler, and retailers. This evaluation was based on the quality standards set by the PGSP and on the previous documented studies on rice quality. The study found that the city-based and municipality-based rice millers have a production capacity at a range of 25-98 kg bag/hr. The Philippine lowland rice varieties used by the rice millers were those with reported to have milling recoveries of 63%-70%; long and slender grains; and intermediate to high amylose content. This study etablished
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Rice -- Philippines -- Quality